Vapor-deposited film, multilayer structure, molded body, food container, and vapor-deposited film production method

By adding a lubricant and a specific amount of titanium compound to the EVOH resin in the base film, the surface smoothness of vapor deposition films is significantly improved, addressing issues of stress concentration and gas barrier property deterioration.

JP2025051649APending Publication Date: 2025-04-04MITSUBISHI CHEM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024161968
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-22
Filing Date
2024-09-19
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing vapor deposition films lack sufficient surface smoothness, which can lead to stress concentration, cracking, and deterioration of gas barrier properties.

Method used

Incorporating a lubricant and a specific amount of titanium compound into the EVOH resin in the base film improves the surface smoothness of the vapor deposited film.

Benefits of technology

The resulting vapor deposition film exhibits excellent surface smoothness, maintaining stable gas barrier properties and preventing cracking over time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025051649000001
    Figure 2025051649000001
Patent Text Reader

Abstract

To provide a vapor-deposited film having excellent surface smoothness; a multilayer structure including the same; a molded body; a food container; and a vapor-deposited film production method.SOLUTION: A vapor-deposited film comprises: a base material film having a layer that contains a composition containing an ethylene-vinyl alcohol copolymer, a lubricant and a titanium compound; and a metal vapor-deposited layer laminated on the base material film. The content of the titanium compound in terms of metals is 0.001 ppm or more and less than 3 ppm relative to the mass of the composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a deposited film, a multilayer structure, a molded article, a food container, and a method for producing a deposited film, and more specifically to a deposited film, a multilayer structure, a molded article, a food container, and a method for producing a deposited film, which have excellent surface smoothness. [Background technology]

[0002] Ethylene-vinyl alcohol copolymers (hereinafter sometimes referred to as "EVOH resins") have very strong intermolecular forces due to hydrogen bonds between hydroxyl groups present in the polymer side chains. As a result, they are highly crystalline, and because the intermolecular forces are also strong in the amorphous parts, films using EVOH resins are difficult for gas molecules to pass through, and they exhibit excellent gas barrier properties. For this reason, EVOH resins are used as gas barrier layers to impart gas barrier properties to multilayer structures such as films and containers in a wide range of fields, such as food packaging.

[0003] Aluminum foil has been used mainly as a gas barrier material in high humidity environments, but because aluminum has high thermal conductivity and poor heat insulation performance, high gas barrier films with thin metal deposition layers are being considered as an alternative to aluminum foil.

[0004] For example, Patent Documents 1 and 2 disclose a vapor-deposited film that is capable of suppressing the occurrence of pinholes and cracks during vapor-deposited film processing such as lamination and suppressing the deterioration of gas barrier properties, and that has a metal vapor-deposited layer on a base film containing EVOH resin and has an average particle size in a specific range. In this technology, it is described that the EVOH resin may contain 0.001 to 1 mass % of inorganic oxide (equivalent to 10 to 10,000 ppm when converted) (Patent Documents 1 and 2: paragraphs

[0017] and

[0018] ). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2017-100451 A [Patent Document 2] International Publication No. 2013 / 125564 Summary of the Invention [Problem to be solved by the invention]

[0006] However, Patent Documents 1 and 2 do not consider the surface smoothness of the vapor-deposited film, and there is a risk of minute irregularities occurring on the surface of the vapor-deposited film. A vapor-deposited film with excellent surface smoothness can suppress stress concentration due to external stress during transportation, prevent cracks from occurring, suppress deterioration of gas barrier properties, and maintain stable performance for a long period of time. Therefore, Patent Documents 1 and 2 state that there is room for improvement in the surface smoothness of the vapor-deposited film.

[0007] The present invention has been made in view of the above problems, and has an object to provide a deposited film having excellent surface smoothness of the deposition surface, a multilayer structure, a molded article, and a food container each containing the deposited film, and a method for producing the deposited film. [Means for solving the problem]

[0008] However, in light of these circumstances, the present inventors conducted extensive research and discovered that by adding a lubricant and a specific trace amount of a titanium compound to the EVOH resin in the base film, the surface smoothness of the vapor-deposited surface of the resulting vapor-deposited film can be made smoother.

[0009] That is, the present invention has the following aspects. [1] A vapor-deposited film comprising a substrate film having a layer containing a composition that contains an EVOH resin, a lubricant, and a titanium compound, and a metal vapor-deposited layer laminated on the substrate film, wherein the content of the titanium compound in terms of metal is 0.001 ppm or more and less than 3 ppm relative to the mass of the composition. [2] The vapor-deposited film according to [1], wherein the content of the lubricant is 500 ppm or less based on the mass of the composition. [3] The vapor-deposited film according to [1] or [2], wherein a mass ratio of the content of the lubricant to the content of the titanium compound calculated as metal is 0.3 to 500,000. [4] The deposited film according to any one of [1] to [3], wherein the base film is a multilayer film further having a layer containing a thermoplastic resin. [5] The vapor-deposited film according to any one of [1] to [4], wherein the metal of the metal vapor-deposited layer is at least one selected from the group consisting of aluminum, gold, silver, copper, titanium, nickel, chromium, tin, and indium. [6] A multilayer structure comprising the vapor-deposited film according to any one of [1] to [5]. [7] A molded article comprising the vapor-deposited film according to any one of [1] to [5]. [8] [6] A food container comprising the multilayer structure described above. [9] The method for producing a vapor-deposited film according to any one of [1] to [5], further comprising a step of laminating an inorganic vapor-deposited layer on the base film. Effect of the Invention

[0010] The vapor-deposited film of the present invention has an excellent surface smoothness on the vapor-deposited surface. Furthermore, multilayer structures, molded articles and food containers each containing such a vapor-deposited film also have an excellent surface smoothness on the vapor-deposited surface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described below based on examples of the mode for carrying out the present invention. However, the present invention is not limited to the embodiment described below.

[0012] In this specification, when expressed as "X to Y" (X and Y are arbitrary numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably more than X" or "preferably less than Y". Furthermore, when it is expressed as "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the meaning of "preferably more than X" or "preferably less than Y." In addition, "x and / or y (x and y are optional configurations)" means at least one of x and y, and can mean three possibilities: x only, y only, and x and y. In the present specification, the upper or lower limit of a numerical range described in stages can be arbitrarily combined with the upper or lower limit of a numerical range of another stage. In addition, in the numerical range described in this specification, the upper or lower limit of the numerical range can be replaced with a value shown in the examples.

[0013] In the present invention, the term "film" includes the meanings of "tape" and "sheet".

[0014] Hereinafter, the monomer units contained in the EVOH resin or the thermoplastic resin may be simply referred to as “units.” For example, a monomer unit based on ethylene may be referred to as an “ethylene unit.”

[0015] <<Deposition film>> A vapor-deposited film according to one embodiment of the present invention (hereinafter, may be referred to as "the present vapor-deposited film") comprises a base film and a vapor-deposited metal layer laminated on the base film. Each component will be described below.

[0016] <Base film> The substrate film has a layer containing an EVOH resin (hereinafter, referred to as "EVOH layer"). Each component of the base film will be described below.

[0017] [EVOH layer] The EVOH layer is formed from a composition containing an EVOH resin (hereinafter, may be referred to as "the composition"). The composition will be described below.

[0018] The composition contains an EVOH resin as a main component, a lubricant, and a specific trace amount of a titanium compound. That is, in the present composition, the base resin is an EVOH resin, and the content of the EVOH resin in the present composition is usually 70 mass % or more, preferably 80 mass % or more, more preferably 90 mass % or more, and particularly preferably 95 mass % or more. Each component will be described below.

[0019] (EVOH resin) The EVOH resin used in the present embodiment is generally a resin obtained by saponifying an ethylene-vinyl ester copolymer, which is a copolymer of ethylene and a vinyl ester monomer, and is a water-insoluble thermoplastic resin.

[0020] As the vinyl ester monomer, vinyl acetate is typically used because of its good market availability and efficiency in treating impurities during production. Examples of vinyl ester monomers other than vinyl acetate include aliphatic vinyl esters such as vinyl formate, vinyl propionate, vinyl valerate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl caprate, vinyl laurate, vinyl stearate, and vinyl versatate, and aromatic vinyl esters such as vinyl benzoate. In general, aliphatic vinyl esters having 3 to 20 carbon atoms, preferably 4 to 10 carbon atoms, and particularly preferably 4 to 7 carbon atoms are used. These are usually used alone, but multiple types may be used simultaneously as necessary.

[0021] The polymerization method for copolymerizing the ethylene and the vinyl ester monomer can be any known polymerization method, such as solution polymerization, suspension polymerization, emulsion polymerization, etc., but solution polymerization using methanol as a solvent is generally used. The saponification of the obtained ethylene-vinyl ester copolymer can also be carried out by a known method. The EVOH resin produced in this manner is mainly composed of structural units derived from ethylene and vinyl alcohol structural units, and also contains a small amount of vinyl ester structural units that remain unsaponified.

[0022] The content of the ethylene structural unit in the EVOH resin is usually 20 to 60 mol%, preferably 25 to 50 mol%, particularly preferably 25 to 35 mol%. The content of the ethylene structural unit can be controlled by the ethylene pressure when the vinyl ester monomer and ethylene are copolymerized. If the content is too low, the gas barrier property and melt moldability under high humidity tend to decrease, whereas if the content is too high, the gas barrier property tends to decrease. The content of the ethylene structural unit can be measured based on ISO14663.

[0023] The saponification degree of the EVOH resin is usually 90 to 100 mol%, preferably 95 to 100 mol%, and particularly preferably 99 to 100 mol%. The saponification degree can be controlled by the amount, temperature, time, etc. of a saponification catalyst (usually an alkaline catalyst such as sodium hydroxide is used) used when saponifying an ethylene-vinyl ester copolymer, and if the saponification degree is too low, the gas barrier properties, heat stability, moisture resistance, etc. tend to decrease. The degree of saponification of the EVOH resin can be measured based on JIS K6726 (however, the EVOH resin is used as a solution uniformly dissolved in a water / methanol solvent).

[0024] The melt flow rate (MFR) of the EVOH resin (210°C, load 2160 g) is usually 0.5 to 100 g / 10 min, preferably 1 to 50 g / 10 min, and particularly preferably 3 to 35 g / 10 min. If the MFR is too high, the stability during film formation tends to be impaired, and if it is too low, the viscosity tends to be too high, making melt extrusion difficult. The MFR is an index of the degree of polymerization of the EVOH resin, and can be adjusted by the amount of the polymerization initiator and the amount of the solvent used when copolymerizing ethylene with a vinyl ester monomer. In this specification, the MFR can be determined by measuring the rate at which a sample flows through an orifice having a length of 8 mm and a hole diameter of 2.095 mm under conditions of a temperature of 210°C and a load of 2160 g using an automatic melt flow rate tester (manufactured by Toyo Seiki Co., Ltd.).

[0025] The EVOH resin may further contain structural units derived from the comonomers shown below (for example, 10 mol % or less of the EVOH resin) to the extent that the effects of the present invention are not impaired. Examples of the comonomer include olefins such as propylene, 1-butene, and isobutene; hydroxyl-containing α-olefins such as 3-butene-1-ol, 3-butene-1,2-diol, 4-pentene-1-ol, and 5-hexene-1,2-diol, and derivatives thereof such as esters and acylation products; hydroxyalkylvinylidenes such as 2-methylenepropane-1,3-diol and 3-methylenepentane-1,5-diol; 1,3-diacetoxy-2-methylenepropane, 1,3-dipropionyloxy-2-methylenepropane, and 1,3-dibutyloxy. hydroxyalkylvinylidene diacetates such as aryloxy-2-methylenepropane; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, (anhydrous) phthalic acid, (anhydrous) maleic acid, (anhydrous) itaconic acid, or their salts or mono- or dialkyl esters having an alkyl group with 1 to 18 carbon atoms; acrylamide, N-alkylacrylamide having an alkyl group with 1 to 18 carbon atoms, N,N-dimethylacrylamide, 2-acrylamidopropanesulfonic acid or its salts, acrylamidopropyldimethylamine or its acid salts or its quaternary salts. acrylamides such as methacrylamide, N-alkyl methacrylamides having an alkyl group with 1 to 18 carbon atoms, N,N-dimethyl methacrylamide, 2-methacrylamidopropanesulfonic acid or its salts, methacrylamidepropyldimethylamine or its acid salts or its quaternary salts; N-vinyl amides such as N-vinylpyrrolidone, N-vinylformamide, and N-vinylacetamide; vinyl cyanides such as acrylonitrile and methacrylonitrile; alkyl vinyl ethers having an alkyl group with 1 to 18 carbon atoms, hydrochloride, etc. vinyl ethers such as alkoxyalkyl vinyl ether and alkoxyalkyl vinyl ether; halogenated vinyl compounds such as vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride and vinyl bromide; vinyl silanes such as trimethoxyvinylsilane; halogenated allyl compounds such as allyl acetate and allyl chloride; allyl alcohols such as allyl alcohol and dimethoxyallyl alcohol; and comonomers such as trimethyl-(3-acrylamido-3-dimethylpropyl)-ammonium chloride and acrylamido-2-methylpropanesulfonic acid.These can be used alone or in combination of two or more.

[0026] Among them, hydroxyl group-containing α-olefins are preferred, and 3-butene-1,2-diol and 5-hexene-1,2-diol are particularly preferred. When the hydroxyl group-containing α-olefins are copolymerized, the resulting EVOH resin has a primary hydroxyl group in the side chain. Such an EVOH resin having a primary hydroxyl group in the side chain, particularly an EVOH resin having a 1,2-diol structure in the side chain, is preferred in that it has good secondary moldability while maintaining gas barrier properties.

[0027] When the EVOH resin has a primary hydroxyl group in a side chain, the content of the structural unit derived from the monomer having the primary hydroxyl group is usually 0.1 to 20 mol %, preferably 0.5 to 15 mol %, and particularly preferably 1 to 10 mol % of the EVOH resin.

[0028] As the EVOH resin, there can also be used EVOH resins that have been "post-modified" by esterification, urethanization, acetalization, cyanoethylation, oxyalkylenation, or the like.

[0029] When the post-modified EVOH resin is used, the modification rate is usually 10 mol% or less, and preferably 4 mol% or less. If the modification rate of the EVOH resin is too high, it tends to be easily thermally deteriorated and the surface smoothness tends to decrease.

[0030] Furthermore, the EVOH resin may be a mixture of EVOH resins having different contents of ethylene structural units, degrees of saponification, degrees of polymerization, copolymerization components, and the like.

[0031] (lubricant) The lubricant may, for example, be a higher fatty acid having 12 to 25 carbon atoms, preferably 13 to 23 carbon atoms, and more preferably 15 to 20 carbon atoms. Examples of the higher fatty acids include higher fatty acids such as lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, and oleic acid; metal salts of higher fatty acids such as aluminum salts, calcium salts, zinc salts, magnesium salts, and barium salts of these higher fatty acids; esters of higher fatty acids such as methyl esters, isopropyl esters, butyl esters, and octyl esters of the higher fatty acids; saturated higher fatty acid amides such as stearic acid amide and behenic acid amide; unsaturated higher fatty acid amides such as oleic acid amide and erucic acid amide; and amides of higher fatty acids such as bis-higher fatty acid amides such as ethylene bisstearic acid amide, ethylene bisoleic acid amide, ethylene biserucic acid amide, and ethylene bislauric acid amide. Examples of lubricants other than the higher fatty acids include low molecular weight polyethylene and low molecular weight polypropylene having a molecular weight of about 500 to 10,000, or low molecular weight polyolefins such as acid-modified products thereof, higher alcohols, ester oligomers, and fluoroethylene resins. These lubricants can be used alone or in combination of two or more kinds.

[0032] From the viewpoints of extrusion stability and market availability, the valence of the higher fatty acids is usually 1 to 5, preferably 1 to 3, and particularly preferably 1 to 2. The valence means the number of structures derived from higher fatty acids in one molecule of the compound used in the lubricant, and for example, when bisstearic acid amide is used as the lubricant, it has two structures derived from higher fatty acid molecules having 18 carbon atoms in one molecule, so it is an amide of a higher fatty acid having 18 carbon atoms, and the valence of the higher fatty acid is 2.

[0033] Among the above-mentioned lubricants, preferred are higher fatty acids, metal salts of higher fatty acids, esters of higher fatty acids, and amides of higher fatty acids, particularly preferred are metal salts of higher fatty acids and amides of higher fatty acids, and from the viewpoint of extrusion stability, more preferably amides of higher fatty acids, and particularly preferably ethylene bisstearamide.

[0034] The lubricant may be in any form, such as a solid (powder, fine powder, flakes, etc.), semisolid, liquid, paste, solution, emulsion (aqueous dispersion), etc. Among these, a powder form is preferred. The particle size of the powder lubricant is usually 0.1 to 100 μm, preferably 1 to 75 μm, and particularly preferably 5 to 50 μm.

[0035] By incorporating an appropriate amount of lubricant in the present composition, the thermal stability is improved, the occurrence of streaks and microgels is suppressed, and the surface becomes smooth. The content of the lubricant is preferably 500 ppm or less, more preferably 300 ppm or less, and particularly preferably 200 ppm or less, based on the mass of the composition. If the content of the lubricant exceeds the above value, the surface smoothness tends to decrease due to a decrease in thermal stability (gel generation). The lower limit of the content of the lubricant is usually 1 ppm, preferably 10 ppm or more, and particularly preferably 50 ppm or more. If no lubricant is added or if the amount is too small, the moldability of the composition tends to decrease.

[0036] The content of the lubricant can be measured, for example, by the following method. When the lubricant is applied to the surface of the EVOH resin, the amount of the lubricant added can be considered as the content. Furthermore, when a lubricant is contained in the composition, if the lubricant is, for example, a higher fatty acid amide, the total amount of nitrogen in the composition can be measured using a total nitrogen trace analyzer and converted into the lubricant content, thereby measuring the lubricant content in the composition.

[0037] (Titanium compounds) The titanium compound may be, for example, an inorganic titanium compound or an organic titanium compound. The titanium compounds may be used alone or in combination of two or more kinds. Among them, inorganic titanium compounds are preferred.

[0038] Examples of the inorganic titanium compound include titanium oxide, titanium hydroxide, titanium chloride, and inorganic salts of titanium. Examples of the titanium oxide include titanium oxide (II), titanium oxide (III), titanium oxide (IV), and titanium suboxide. Examples of the titanium hydroxide include titanium(I) hydroxide and titanium(II) hydroxide. Examples of the titanium chloride include titanium(I) chloride and titanium(II) chloride. The inorganic salts of titanium are those other than the titanium chloride, and examples thereof include titanium phosphate and titanium sulfate. Among these, titanium oxide is preferred, titanium(IV) oxide is more preferred, and rutile-type titanium(IV) oxide is particularly preferred.

[0039] Examples of the organic titanium compound include titanium carboxylates such as titanium acetate, titanium butyrate, and titanium stearate.

[0040] In addition to being present as a titanium compound in the present composition, the titanium compound may be present in an ionized state or in the form of a complex interacting with the EVOH resin or other ligands.

[0041] The average particle size of the titanium compound is usually 0.001 to 100 μm, preferably 0.01 to 50 μm, and more preferably 0.015 to 20 μm. When the average particle size of the titanium compound is within the above range, the effect of suppressing surface irregularities tends to be excellent. The average particle size of the titanium compound can be measured by a laser diffraction type particle size distribution measuring device or the like. The average particle size here refers to the median diameter.

[0042] The content of the titanium compound calculated as metal is 0.001 ppm or more and less than 3 ppm based on the mass of the composition. It is preferably 0.01 to 1 ppm, more preferably 0.03 to 0.5 ppm, and particularly preferably 0.05 to 0.2 ppm. By setting the content of the titanium compound within the above range, the titanium compound fills up minute dents on the surface of the EVOH film, resulting in excellent surface smoothness. If the content of the titanium compound is too low, the minute dents are not filled up, leaving minute irregularities on the surface, and if the content is too high, the remaining titanium oxide appears on the surface, forming convex parts and causing the surface to become rough. The metal-equivalent content of the titanium compound is the content of titanium element.

[0043] In addition, by setting the content of the titanium compound within the above range, it is possible to suppress the generation of microgels due to thermal deterioration during melt molding, and the smoothness of the film surface tends to be excellent.In addition, if the content of the titanium compound is too low, the effect of suppressing the generation of microgels decreases, and the surface smoothness tends to decrease, while if the content is too high, the EVOH resin is easily decomposed, and the surface smoothness tends to decrease due to the generation of microgels.

[0044] The content of the titanium compound in terms of metal can be quantified by weighing the composition into a platinum crucible, incinerating it using a burner and an electric furnace, decomposing the incinerated product by heating it with nitric acid and hydrofluoric acid, treating it with a mixed acid of dilute nitric acid and dilute hydrofluoric acid, and measuring the titanium in the constant volume solution obtained by constant volume measurement using an ICP mass spectrometer (Agilent 8800, manufactured by Agilent Technologies) by ICP mass spectrometry.

[0045] The mass ratio of the content of the lubricant to the content of the titanium compound in terms of metal [lubricant content / metal content of titanium compound] is usually 0.3 to 500000, preferably 1 to 50000, more preferably 20 to 10000, particularly preferably 250 to 4000, and especially preferably 900 to 3000. If this value is too large, thermal stability tends to be hindered, and if it is too small, surface smoothness tends to decrease.

[0046] Normally, when a titanium compound is added to a resin composition containing an EVOH resin, it is considered that the titanium ions will cause thermal degradation of the resin composition and generate microgels, and therefore it is common technical knowledge for a person in this field to avoid using titanium compounds. However, in this embodiment, contrary to such common technical knowledge, it has been found that when a specific trace amount of a titanium compound is used, the titanium of the titanium compound is coordinated to the double bond of the main chain of the EVOH resin to form a chelate, etc., thereby improving thermal stability, suppressing the generation of microgels due to thermal degradation, and providing an EVOH film with excellent surface smoothness.

[0047] In addition, EVOH resin becomes discolored due to thermal degradation. This is presumably because EVOH resin deteriorates due to heat, generating radicals, which dehydrate the hydroxyl groups in the EVOH resin, generating double bonds in the main chain of the EVOH resin, and these sites become reaction starting points, which further promote dehydration and form conjugated polyene structures in the main chain of the EVOH resin. In addition, in this resin composition, titanium in the specific trace amount of titanium compound is stabilized as a tetravalent ion, so that even a trace amount of titanium is stabilized by coordinating with the double bonds in the main chain of the EVOH resin to form a chelate, etc., thereby suppressing the formation of a polyene structure.

[0048] (Other thermoplastic resins) The present composition may contain a thermoplastic resin other than EVOH resin within a range that does not impair the effects of the present invention (for example, typically 30 mass% or less of the present composition, preferably 20 mass% or less, particularly preferably 10 mass% or less, the lower limit being typically 0 mass%). As the other thermoplastic resin, known thermoplastic resins can be used, such as polyester resins, polystyrene resins, polyvinyl chloride resins, polycarbonate resins, ionomers, polyvinylidene chloride, polyester elastomers, polyurethane elastomers, chlorinated polyethylene, chlorinated polypropylene, etc. These can be used alone or in combination of two or more kinds.

[0049] (Other compounding agents) The composition may contain additives (excluding titanium compounds and lubricants) that are generally blended with EVOH resins, within a range that does not impair the effects of the present invention (for example, usually 30% by mass or less of the resin composition, preferably 20% by mass or less, more preferably 10% by mass or less, the lower limit being usually 0% by mass). Examples of the additives include inorganic double salts (for example, hydrotalcite, etc.), plasticizers (for example, aliphatic polyhydric alcohols such as ethylene glycol, glycerin, hexanediol, etc.), oxygen absorbers [for example, inorganic oxygen absorbers such as aluminum powder and potassium sulfite; ascorbic acid, further its fatty acid esters and metal salts, etc., gallic acid, polyhydric phenols such as hydroxyl group-containing phenol aldehyde resins, terpene compounds, blends of tertiary hydrogen-containing resins and transition metals (for example, a combination of polypropylene and cobalt), carbon-carbon unsaturated bond-containing resins and transition metals, and the like. Blends with transition metals (e.g., a combination of polybutadiene and cobalt), photooxidative decomposition resins (e.g., polyketones), anthraquinone polymers (e.g., polyvinyl anthraquinone), and the like, and further, polymer-based oxygen absorbers such as those obtained by adding photoinitiators (e.g., benzophenone) and antioxidants other than those mentioned above and deodorants (e.g., activated carbon) to these blends, heat stabilizers, light stabilizers, ultraviolet absorbers, colorants, antistatic agents, surfactants (excluding those used as lubricants), antibacterial agents, antiblocking agents, and fillers (e.g., inorganic fillers, etc.) may be blended. These compounds may be used alone or in combination of two or more.

[0050] (Method of producing the composition) The composition can be produced, for example, by mixing the EVOH resin, the lubricant, and the titanium compound by a known method, such as a dry blend method, a melt mixing method, a solution mixing method, an impregnation method, etc. Among these, it is preferable to produce the composition by a process including a step of melt mixing the composition raw material containing the EVOH resin and the titanium compound. Also, these production methods can be arbitrarily combined.

[0051] The dry blending method may, for example, be (i) a method in which a pellet-shaped EVOH resin is dry-blended with a lubricant and a titanium compound using a tumbler or the like.

[0052] Examples of the melt mixing method include (ii) a method in which a pellet-shaped EVOH resin is dry-blended with a lubricant and a titanium compound, and the resulting mixture is melt-kneaded; and (iii) a method in which a lubricant and a titanium compound are added to a molten EVOH resin, and the mixture is melt-kneaded.

[0053] Examples of the solution mixing method include (iv) a method in which a solution is prepared using a commercially available EVOH resin, a lubricant and a titanium compound are added thereto, the solution is solidified and molded, and then the solution is subjected to solid-liquid separation by known means and dried; and (v) a method in which a lubricant and a titanium compound are added to an ethylene-vinyl ester copolymer solution before saponification or a homogeneous solution of an EVOH resin (such as a water / alcohol solution) during the production process of an EVOH resin, the solution is solidified and molded, and then the solution is subjected to solid-liquid separation by known means and dried.

[0054] The impregnation method includes, for example, (vi) a method in which pelletized EVOH resin is contacted with an aqueous solution containing a lubricant and a titanium compound to incorporate the lubricant and titanium compound into the EVOH resin, and then dried. The aqueous solution containing the titanium compound may be an aqueous solution of a lubricant and a titanium compound, or an aqueous solution of a lubricant and a titanium compound immersed in water containing various chemicals to elute titanium ions.

[0055] In the impregnation method, the content (in terms of metal) of the lubricant and titanium compound can be controlled by the concentration of the lubricant and titanium compound in the aqueous solution in which the EVOH resin is immersed, the immersion temperature, the immersion time, etc. The immersion temperature and immersion time are usually 0.5 to 48 hours, preferably 1 to 36 hours, and the immersion temperature is usually 10 to 40°C, preferably 20 to 35°C.

[0056] As the drying method in each of the above-mentioned production methods, various drying methods can be used, and either stationary drying or fluidized drying may be used. These methods may also be used in combination.

[0057] As described above, in this embodiment, the above different methods can be combined. Among them, the melt mixing method is preferred, and method (ii) is particularly preferred, in terms of productivity and the fact that a resin composition with more remarkable effects of the present invention can be obtained. In addition, when using the other thermoplastic resins and other compounding agents, they may be compounded by a conventional method according to the above manufacturing method.

[0058] The composition of the present invention obtained by each of the above-mentioned production methods may have any shape, but is preferably in the form of pellets. The pellets may be, for example, spherical, oval, cylindrical, cubic, or rectangular, but are usually oval or cylindrical, and from the viewpoint of convenience when used later as a molding material, the size of the pellets is usually 1 to 10 mm, preferably 2 to 6 mm, and more preferably 2.5 to 5.5 mm for the short diameter in the case of an oval shape, and usually 1.5 to 30 mm, preferably 3 to 20 mm, and more preferably 3.5 to 10 mm for the long diameter in the case of a cylindrical shape, from the viewpoint of convenience when used later as a molding material. Also, the diameter of the base is usually 1 to 6 mm, preferably 2 to 5 mm, and the length is usually 1 to 6 mm, preferably 2 to 5 mm. Moreover, it is preferable that the shape and size of the pelletized EVOH resin used in each of the above-mentioned production methods are the same.

[0059] The water content of the present composition before melt molding is usually from 0.01 to 0.5% by mass, preferably from 0.05 to 0.35% by mass, and particularly preferably from 0.1 to 0.3% by mass. Here, the term "melt molding" before melt molding refers to melting and forming a certain shape, and examples of this include melting a resin composition and forming it into pellets, or melting a resin composition and forming it into a film.

[0060] The water content of the composition is measured and calculated by the following method. The mass (W1) of this composition before drying is weighed on an electronic balance, dried in a hot air dryer at 150°C for 5 hours, and then cooled in a desiccator for 30 minutes, after which the mass (W2) is weighed and calculated using the following formula. Moisture content (mass%)=[(W1-W2) / W1]×100

[0061] The composition thus obtained is prepared into various forms, such as pellets, powder, or liquid, and is provided as a molding material for various molded products. In particular, in the present embodiment, when the composition is provided as a material for melt molding, the effects of the present invention tend to be more efficiently obtained, which is preferable. The present composition also includes resin compositions obtained by mixing a resin other than the EVOH resin used in the present composition.

[0062] The substrate film may be, for example, a single-layer film (EVOH layer) formed from the present composition, or a multilayer film having at least one EVOH layer.

[0063] [Layer containing thermoplastic resin] The base film preferably has a layer containing a thermoplastic resin (hereinafter, sometimes referred to as a "thermoplastic resin layer"). When the base film has a thermoplastic resin layer, the mechanical strength and barrier properties against water vapor of the vapor-deposited film tend to be further improved. In addition, properties such as heat sealability and mechanical strength can be imparted depending on the type of thermoplastic resin constituting the thermoplastic resin layer.

[0064] The thermoplastic resin is one other than the EVOH resin, and examples thereof include polyolefins such as linear low-density polyethylene, low-density polyethylene, very low-density polyethylene, medium-density polyethylene, high-density polyethylene, etc., ethylene-vinyl acetate copolymers, ionomers, ethylene-propylene (block or random) copolymers, ethylene-(meth)acrylic acid copolymers, ethylene-(meth)acrylic acid ester copolymers, polypropylene, propylene-α-olefin copolymers, polybutene, polypentene, etc., or polyolefins graft-modified with unsaturated carboxylic acids or their esters; polyesters; polyamides (including copolymerized polyamides); polyvinyl chloride; polyvinylidene chloride; acrylic resins; polystyrene; polyvinyl esters; polyester elastomers; polyurethane elastomers; chlorinated polystyrene; chlorinated polypropylene; aromatic polyketones or aliphatic polyketones, and polyalcohols obtained by reducing these; polyacetals; polycarbonates, etc. Among these, from the viewpoint of excellent heat sealability and mechanical properties, polyolefins are preferred, polypropylene and polyethylene are more preferred, and polyethylene is particularly preferred. These can be used alone or in combination of two or more. Incidentally, linear low density polyethylene, low density polyethylene, very low density polyethylene, medium density polyethylene, and high density polyethylene are terms commonly used to represent types of polyethylene.

[0065] When polyethylene is used as the thermoplastic resin, the melt flow rate (MFR) of the polyethylene measured in accordance with JIS K 7210: 2014 (190°C, load 2.16 kg) is preferably 0.10 to 7.5 g / 10 min, more preferably 0.15 to 5.0 g / 10 min, and particularly preferably 0.2 to 2.5 g / 10 min. If the MFR of the polyethylene is within the above range, molding stability tends to be improved.

[0066] The content of the thermoplastic resin in the thermoplastic resin layer is not particularly limited, but it is preferable that the thermoplastic resin is the main component (i.e., the content of the thermoplastic resin contained in the thermoplastic resin layer is 50% by mass or more). The content of the thermoplastic resin is more preferably 60% by mass or more, further preferably 70% by mass or more, particularly preferably 80% by mass or more, 90% by mass or more, 95% by mass or more, and particularly preferably 100% by mass.

[0067] The thermoplastic resin layer may contain components other than the thermoplastic resin, such as antiblocking agents, processing aids, resins other than thermoplastic resins, carboxylic acid compounds, phosphoric acid compounds, boron compounds, metal salts, stabilizers, antioxidants, UV absorbers, plasticizers, antistatic agents, lubricants, colorants, fillers, surfactants, drying agents, crosslinking agents, reinforcing agents such as various fibers, etc., within a range that does not impair the effects of the present invention, generally within a range of 20 mass % or less. These may be used alone or in combination of two or more kinds.

[0068] [Layer containing adhesive resin] The substrate film may have a layer containing an adhesive resin (hereinafter, may be referred to as an "adhesive resin layer"). When the substrate film has an adhesive resin layer, the appearance characteristics (film surface) of the present deposition film tend to be better.

[0069] The adhesive resin is not particularly limited, but is preferably a polyolefin having a carboxy group, a carboxylic anhydride group, or an epoxy group, and more preferably a polyolefin having a carboxylic anhydride group. Such adhesive resins tend to have excellent adhesion to the EVOH layer and / or the thermoplastic resin layer.

[0070] Examples of polyolefins containing carboxyl groups include polyolefins copolymerized with acrylic acid or methacrylic acid. In this case, all or part of the carboxyl groups contained in the polyolefin may be present in the form of a metal salt, as typified by ionomers. Examples of polyolefins having carboxylic anhydride groups include polyolefins graft-modified with maleic anhydride or itaconic acid. Examples of polyolefins having epoxy groups include polyolefins copolymerized with glycidyl methacrylate. Among these, polyolefins having carboxylic anhydride groups such as maleic anhydride, and particularly polyethylene having carboxylic anhydride groups, can be used. These can be used alone or in combination of two or more kinds.

[0071] The melt flow rate (MFR) of the adhesive resin measured according to JIS K 7210:2014 (190°C, load 2.16 kg) is not particularly limited, but is preferably 0.1 to 20.0 g / 10 min, more preferably 1.0 to 10.0 g / 10 min. When the MFR of the adhesive resin is within the above range, molding stability tends to be improved.

[0072] The content of the adhesive resin in the adhesive resin layer is not particularly limited, but it is preferable that the adhesive resin is the main component (i.e., the content of the adhesive resin contained in the adhesive resin layer is 50% by mass or more). In particular, the content of the adhesive resin is more preferably 60% by mass or more, even more preferably 70% by mass or more, and particularly preferably 80% by mass or more, 90% by mass or more, 95% by mass or more, or 100% by mass.

[0073] The adhesive resin layer may contain components other than the adhesive resin, such as antiblocking agents, processing aids, resins other than the adhesive resin, carboxylic acid compounds, phosphoric acid compounds, boron compounds, metal salts, stabilizers, antioxidants, UV absorbers, plasticizers, antistatic agents, lubricants, colorants, fillers, surfactants, drying agents, crosslinking agents, reinforcing agents such as various fibers, etc., within a range that does not impair the effects of the present invention, generally within a range of 20 mass % or less. These may be used alone or in combination of two or more kinds.

[0074] [Method of manufacturing base film] The substrate film can usually be produced by extruding the composition through a die, forming it into a film, and, if necessary, uniaxially stretching it. In addition, when the base film has a thermoplastic resin layer or an adhesive resin layer, the base film can be produced by forming each raw material composition forming the EVOH layer, the thermoplastic resin layer, and the adhesive resin layer into a film by conventional coextrusion in which the raw material compositions are extruded from separate dies or a common die and laminated, and then stretching the film as necessary. As the die, for example, a circular die or a T-die can be used. Examples of the molding method include melt molding methods such as extrusion molding, blow molding, injection molding, thermoforming, and inflation molding, and solution molding methods such as cast molding.

[0075] The substrate film may have an EVOH layer, and other layer configurations are not particularly limited, but it is preferable that at least one of the surface layers is an EVOH layer. Since the substrate film has an EVOH layer, the present vapor-deposited film having excellent transparency can be obtained. The base film is preferably multilayered. When the EVOH layer is the "(A) layer", the thermoplastic resin layer is the "(B) layer", and the adhesive resin layer is the "(C) layer", examples of the layer configuration include (B) layer / (A) layer, (B) layer / (A) layer / (B) layer, (B) layer / (C) layer / (A) layer / (B) layer, (B) layer / (C) layer / (A) layer / (C) layer / (B) layer, (B) layer / (A) layer / (B) layer / (A) layer / (B) layer, (B) layer / (B) layer / (B) layer / (C) layer / (A) layer / (C) layer / (B) layer, (A) layer / (C) layer / (B) layer / (B) layer, (A) layer / (C) layer / (B) layer, (A) layer / (C) layer / (B) layer, (A) layer / (C) layer / (B) layer, (A) layer / (C) layer / (B) layer, (A) layer / (B ... and the like.

[0076] In the above examples, layers (B) and (C) are exemplified as layers other than layer (A), but layers other than layer (A) are not limited to these. Moreover, it is preferable that the base film does not include a layer formed from a resin composition containing a polyamide-based resin as a main component (that is, a resin composition containing 50% by mass or more of a polyamide-based resin). In the above examples, the " / " sign means that the layers on both sides of the " / " sign are directly laminated.

[0077] The substrate film thus obtained is preferably stretched as necessary, more preferably uniaxially stretched. The stretching ratio of the uniaxially stretched film is preferably at least 3, more preferably at least 4, and particularly preferably at least 5. If the stretching ratio is less than 3, thickness unevenness due to stretching tends to occur and gas barrier properties tend to deteriorate. The upper limit of the stretching ratio is preferably 12 times or less, more preferably 10 times or less, and particularly preferably 8 times or less. If the stretching ratio exceeds 12 times, the film surface after stretching tends to deteriorate. By making it into a uniaxially stretched film, there are advantages such as economic efficiency, ease of tearing the multilayer structure (easy opening of the packaging material when used as a packaging material), and improved gas barrier properties.

[0078] The stretching direction of the uniaxially stretched film is not particularly limited and may be either the longitudinal direction (MD direction) or the transverse direction (TD direction). However, uniaxial stretching in the longitudinal direction (MD direction) is preferred, and it is particularly preferred that the film is not substantially stretched in a direction different from the stretching direction. The stretched state of the substrate film (unstretched, uniaxially stretched, biaxially stretched, etc.) can be confirmed by using a general method for analyzing the orientation of a resin (e.g., wide-angle X-ray scattering (WAXS), etc.).

[0079] The stretching method of the uniaxially stretched film is not particularly limited, but examples thereof include tenter stretching, tubular stretching, roll stretching, etc. Among them, from the viewpoint of production cost, uniaxial stretching by roll stretching is preferred. In addition, when the base film is obtained by inflation molding, roll stretching is preferred.

[0080] The stretching temperature during uniaxial stretching is not particularly limited, but is generally 50 to 130°C.

[0081] The total thickness of the base film is not particularly limited and can be appropriately set according to the application. The thickness of the base film is preferably 10 μm or more, more preferably 15 μm or more. When the thickness of the base film is 10 μm or more, industrial productivity and mechanical properties tend to be improved. In addition, the thickness of the base film is preferably 100 μm or less, more preferably 50 μm or less. When the thickness of the base film is 100 μm or less, industrial productivity and economic efficiency tend to be improved. The thickness of the substrate film, which is a uniaxially stretched film, means the thickness after stretching.

[0082] When the base film is a multi-layer film, the thickness of the EVOH layer is preferably 0.5 μm or more, more preferably 0.8 μm or more, and particularly preferably 1 μm or more. When the thickness of the EVOH layer is 0.5 μm or more, the gas barrier property tends to be improved. On the other hand, the thickness of the EVOH layer is preferably 20 μm or less, more preferably 10 μm or less, and particularly preferably 5 μm or less. When the thickness of the EVOH layer is 20 μm or less, the appearance characteristics (film surface) tend to be good. The thickness of the multi-layer film, which is a uniaxially stretched film, means the thickness after stretching. When the EVOH layer is provided in multiple layers on the base film, the total thickness of all the EVOH layers is preferably within the above range.

[0083] When the base film is a multilayer film, the ratio of the thickness of the EVOH layer to the total thickness of all layers is preferably 30% or less, more preferably 20% or less, and may be 10% or less, or 5% or less, from the viewpoints of industrial productivity and mechanical properties.

[0084] When the base film has a thermoplastic resin layer, the thickness thereof is preferably from 7 to 100 μm, more preferably from 10 to 50 μm, from the viewpoints of industrial productivity and mechanical properties. In the case of a substrate film which is a uniaxially stretched film, the thickness of the thermoplastic resin layer means the thickness after stretching. In addition, when the substrate film has multiple thermoplastic resin layers, it is preferable that the total thickness of all the thermoplastic resin layers is in the above range.

[0085] When the base film has an adhesive resin layer, the thickness thereof is preferably from 0.5 to 20 μm, more preferably from 1 to 10 μm, from the viewpoints of industrial productivity and quality stability. In the case of a substrate film that is a uniaxially stretched film, the thickness of the adhesive resin layer means the thickness after stretching. In addition, when the adhesive resin layer is provided in a multi-layer structure on the substrate film, it is preferable that the total thickness of all the adhesive resin layers is in the above range.

[0086] The internal haze value of the substrate film is preferably less than 0.4%, more preferably 0.3% or less, further preferably 0.2% or less, and particularly preferably 0%. Such measurement can be performed using a substrate film having a thickness of 33 μm and a haze meter in accordance with ASTM D1003.

[0087] <Metal deposition layer> The metal vapor deposition layer laminated on the base film is obtained by vapor deposition of a single metal or an alloy of two or more metals. From the viewpoint of gas barrier properties, the metal vapor deposition layer is preferably laminated on the EVOH layer of the base film.

[0088] Examples of metals used in the metal vapor deposition layer include those classified as aluminum group elements (aluminum, gallium, indium, etc.), tin group elements (titanium, zirconium, tin, hafnium, etc.), precious metals (copper, silver, gold, etc.), chromium group elements (chromium, molybdenum, tungsten, etc.), and iron group elements (iron, cobalt, nickel, etc.), and alloys thereof. Among these, at least one selected from the group consisting of aluminum, gold, silver, copper, titanium, nickel, chromium, tin, and indium is preferred from the viewpoints of general availability and ease of handling, and aluminum is particularly preferred.

[0089] The metal used in the metal deposition layer preferably contains a metal compound such as a metal oxide, a metal carbide, a metal nitride, etc., and among these metal compounds, a metal oxide is preferred. The content of such a metal compound is preferably 50% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, and may be 100% by mass, of the metal used in the metal deposition layer.

[0090] The metal vapor deposition layer can be identified by analyzing a cross section of the laminate by energy dispersive spectroscopy (EDS).

[0091] <Method of manufacturing the vapor-deposited film> The present vapor-deposited film can be produced by laminating the above-mentioned metal vapor-deposited layer on the above-mentioned substrate film.

[0092] The method for laminating the metal vapor deposition layer on the base film is not particularly limited, and any known vapor deposition method may be appropriately adopted, for example, a physical vapor deposition method (PVD method) such as a vacuum deposition method, a sputtering method, or an ion plating method, or a chemical vapor deposition method (CVD method).

[0093] The thickness of the metal deposition layer is usually 1 to 100 nm, preferably 3 to 50 nm, and more preferably 5 to 20 nm. If the thickness of the metal deposition layer is less than 1 nm, the gas barrier property tends to be insufficient, while if the thickness exceeds 100 nm, the effect of improving the gas barrier property cannot be obtained, and the bending resistance and production cost tend to be high.

[0094] The present vapor-deposited film thus obtained has excellent surface smoothness of the vapor-deposited surface. The root-mean-square height (Sq) of the vapor-deposited surface of the present vapor-deposited film is preferably 0.080 μm or less, more preferably 0.070 μm or less, and even more preferably 0.065 μm or less. The smaller the root-mean-square height (Sq), the smoother the surface is, which is preferable. The root-mean-square height (Sq) can be measured by the method of ISO25178, specifically, by the method described in the Examples below.

[0095] The arithmetic mean height (Sa) of the deposition surface of the present deposition film is preferably 0.060 μm or less, more preferably 0.055 μm or less, and even more preferably 0.050 μm or less. The smaller the arithmetic mean height (Sa), the smoother the surface is, which is preferable. The arithmetic mean height (Sa) can be measured by the method described in the Examples below. In this specification, the arithmetic mean height (Sa) means the average absolute value of the difference in height between each point and the average plane of the surface of the deposited film.

[0096] The oxygen permeability of this deposition film at 20℃ and 90% RH is 8cc / m 2 ·day·atm or less is preferable, and 7cc / m 2 ·day·atm or less is preferable, 5cc / m 2 ·day·atm or less is particularly preferable.

[0097] The vapor-deposited film of the present invention can be suitably used as a molding for packaging general foods, as well as seasonings such as mayonnaise and dressings, fermented foods such as miso, oily foods such as salad oil, snacks, beverages, cosmetics, medicines, and the like, as well as packaging materials such as packaging films, or as a part of a multilayer structure for forming these.

[0098] <<Multilayer structure>> The multilayer structure is obtained by laminating another layer on the present vapor-deposited film. The other layer to be laminated on the present vapor-deposited film is not particularly limited, and may be a layer formed from a resin composition containing the thermoplastic resin exemplified above as the thermoplastic resin or the adhesive resin exemplified above as the adhesive resin.

[0099] As a method for producing the multilayer structure, various known production methods can be used, such as, for example, a dry lamination method, a sand lamination method, an extrusion lamination method, a coextrusion lamination method, a solution coating method, and the like.

[0100] <<Molded body>> The deposited film or the multilayer structure can be used to obtain a molded product in the shape of a cup or tray. In this case, a drawing method is usually used, specifically, a vacuum forming method, a pressure forming method, a vacuum pressure forming method, a plug-assisted vacuum pressure forming method, etc. Furthermore, it is also possible to obtain molded articles such as tube- or bottle-shaped multilayer containers (laminate structure) and food containers from a multilayer parison (a hollow tubular preform before blowing) using the multilayer structure. In such cases, a blow molding method is usually employed, and specific examples include extrusion blow molding (double-head type, mold moving type, parison shift type, rotary type, accumulator type, horizontal parison type, etc.), cold parison type blow molding, injection blow molding, and biaxial stretch blow molding (extrusion type cold parison biaxial stretch blow molding, injection type cold parison biaxial stretch blow molding, injection molding in-line type biaxial stretch blow molding, etc.). The resulting laminate may be subjected to processes such as heat treatment, cooling, rolling, printing, dry lamination, solution or melt coating, bag making, deep drawing, box processing, tube processing, and splitting, as required. EXAMPLES

[0101] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are based on mass.

[0102] <Example 1> [Preparation of pellets of the composition] As the EVOH resin, pellets of an EVOH resin having an ethylene structural unit content of 29 mol % and a saponification degree of 99.6 mol % were used. Further, ethylene bisstearic acid amide (NOF Corp., Alflow H50-FP) was used as the lubricant, and titanium oxide (FUJIFILM Wako Pure Chemical Industries, Ltd.) was used as the titanium compound. The EVOH resin pellets were dry-blended with the ethylene bisstearic acid amide so that the content was 180 ppm based on the mass of the composition, and with the titanium oxide so that the content, calculated as a metal, was 0.1 ppm based on the mass of the composition, to obtain a mixture. The mixture was fed to a twin-screw extruder (20 mmΦ) equipped with a two-hole die and extruded under the following extrusion conditions, and the extruded strand was air-cooled and solidified on a belt conveyor. The solidified strand was then cut to obtain pellets of the composition. (Extrusion conditions) Extruder setting temperature (℃): C1 / C2 / C3 / C4 / C5 / C6 =150 / 200 / 210 / 210 / 210 / 210

[0103] [Preparation of melt-extruded monolayer film] The pellets of the obtained composition were extruded under the following conditions to obtain a melt-extruded monolayer film. (Film production conditions) Extruder: Brabender Plastograph EC-plus Screw: Single shaft, 20mmΦ, full flight Cylinder temperature setting: 190~210℃ Cooling roll temperature setting: 80℃ Film thickness: 30μm

[0104] [Formation of metal deposition layer] Using a batch-type deposition facility manufactured by Showa Shinku, the monolayer film was used as a substrate film, and a metal deposition layer of aluminum was laminated thereon while the surface temperature of the substrate film was kept at 40° C. or lower, to obtain the deposition film of Example 1.

[0105] <Example 2> A vapor-deposited film was obtained in the same manner as in Example 1, except that the content of titanium oxide in terms of metal was changed to 1 ppm based on the mass of the composition.

[0106] <Comparative Example 1> A vapor-deposited film was obtained in the same manner as in Example 1, except that titanium oxide was not used.

[0107] <Comparative Example 2> A vapor-deposited film was obtained in the same manner as in Example 1, except that the content of titanium oxide in terms of metal was changed to 10 ppm based on the mass of the composition.

[0108] The surface smoothness of the thus obtained deposited films of Examples 1 and 2 and Comparative Examples 1 and 2 was measured as follows. The measurement results are shown in Table 1 below.

[0109] Root mean square height (Sq) and Arithmetic mean height (Sa) The surface of the deposited film on the metal deposition layer side (deposited surface) was observed under the following conditions using a laser microscope (Olympus LEXTOLS5000). Light source: 405nm wavelength light source Objective lens: 100x magnification Optical zoom: 1.0x Image area: 129μm×129μm Resolution: 1024 x 1024 pixels The root mean square height (Sq) and arithmetic mean height (Sa) of the vapor-deposited surface were measured from any point on the vapor-deposited surface using the method of ISO25178. The smaller the root mean square height (Sq), the smoother the surface. Also, the smaller the arithmetic mean height (Sa), the smoother the surface.

[0110] [Table 1]

[0111] The results shown in Table 1 above show that the vapor-deposited films of Examples 1 and 2, which contain a specific trace amount of titanium compound, have small root-mean-square height (Sq) and arithmetic mean height (Sa) and have smooth vapor-deposited surfaces. On the other hand, the vapor-deposited films of Comparative Example 1, which did not contain a titanium compound, and Comparative Example 2, which contained a titanium compound above a specific range, had large root-mean-square height (Sq) and arithmetic mean height (Sa), indicating that the vapor-deposited surface was not smooth.

[0112] In addition, even when the base film constituting the vapor-deposited film of Examples 1 and 2 is a multilayer film obtained by co-extruding the composition and a thermoplastic resin (polyethylene resin, etc.) instead of the above-mentioned single layer film, the effect of excellent surface smoothness of the vapor-deposited surface can be obtained. Furthermore, the effect of excellent surface smoothness of the vapor-deposited surface can also be obtained in the multilayer structures, molded articles, and food containers formed using the vapor-deposited films of Examples 1 and 2. [Industrial Applicability]

[0113] The vapor-deposited film of the present invention can be suitably used as a molding for packaging general foods, as well as seasonings such as mayonnaise and dressings, fermented foods such as miso, oily foods such as salad oil, snacks, beverages, cosmetics, medicines, and the like, as well as packaging materials such as packaging films, or as a part of a multilayer structure for forming these.

Claims

1. The vapor-deposited film includes a substrate film having a layer containing a composition that contains an ethylene-vinyl alcohol copolymer, a lubricant, and a titanium compound, and a metal vapor-deposited layer laminated on the substrate film, wherein the content of the titanium compound in terms of metal is 0.001 ppm or more and less than 3 ppm based on the mass of the composition.

2. The vapor-deposited film according to claim 1 , wherein the content of the lubricant is 500 ppm or less based on the mass of the composition.

3. 3. The vapor-deposited film according to claim 1, wherein a mass ratio of the content of the lubricant to the content of the titanium compound in terms of metal is 0.3 to 500,000.

4. 3. The deposited film according to claim 1, wherein the substrate film is a multilayer film further comprising a layer containing a thermoplastic resin.

5. 3. The vapor-deposited film according to claim 1, wherein the metal of the vapor-deposited metal layer is at least one selected from the group consisting of aluminum, gold, silver, copper, titanium, nickel, chromium, tin, and indium.

6. A multilayer structure comprising the vapor-deposited film according to claim 1 or 2.

7. A molded article comprising the vapor-deposited film according to claim 1 or 2.

8. A food container comprising the multi-layer structure of claim 6.

9. The method for producing a vapor-deposited film according to claim 1 , further comprising a step of laminating an inorganic vapor-deposited layer on the substrate film.

Citation Information

Patent Citations

  • Vapor-deposited film, packaging material, vacuum insulator and manufacturing method of vapor-deposited film

    JP2017100451A

  • Polyvinyl alcohol vapor-deposited film

    WO2013125564A1